A mudança nas rotinas de produção do radiojornalismo a partir do uso do Twitter : o caso da Rádio Gaúcha - Santos, Geórgia Pelissaro dos (2013)
Through the Internet´s development in which Castells (1999) calls Network Society or Information Society, the death of the radio is being discussed again - the first time was when the television appeared, in the 1950s and 1960s. The emergence of social networks exposes the radio as an obsolete vehicle (after all, has only sound), and despite its advantages, needs to reinvent itself again. That s why the radio has joined Twitter. But with this - with the appropriation of a new tool, the work of journalists is affected. In the research that follows, it will be precisely evaluated the impact of Twitter and Radio Gaucha s marriage. With the news making aims to understand how the production routines were changed after the incorporation of Twitter in the daily lives of journalists.